Mudanças estruturais e resultados bancários no mercado de varejo - Rodrigues, Ivanildo de Lima (2017)
In the last decade, the financial system has undergone a series of economic and political changes, as well as structural ones, among them the technological modernization as a factor of optimization of processes and of attendance as well as of new services rendered related. The objective of this study is to verify the effectiveness of investing in information technology (T.I.), investigating whether there is an impact on bank efficiency of the results indicator (ROE) of the five largest financial institutions operating in Brazil; That is, how efficient use of technological resources has affected bank results over the last 10 years and how effective resource allocation is in process automation. Using the database used, it was extracted from the Central Bank of Brazil's website, which periodically makes available the quarterly financial statements of the institutions authorized to operate in the country and the financial statements made available by the institutions containing additional data not contemplated by the BACEN. With the use of the Central Bank of Brazil database, regressions were made seeking to identify the profit and loss accounts that best explain the profitability of the banks, among them the sub-accounts contained in administrative expenses called expenses for data processing and communications. Firstly, an essay was made on the evolution of institutions of interest addressing structural changes such as the evolution of the number of self-service terminals, internet banking and mobile, as well as the number of traditional service points and number of employees. Next, the Return on Equity (ROE) indicators were examined, observing their evolution in the period of interest, seeking to identify which factors affected it and ROE, respectively. It was also verified the evolution of CAPEX (Capital Expenditure) and OPEX (Operational Expenditure) in data processing of each institution, although in different approaches. In the end, greater cohesion was identified between private institutions and higher general revenues, with public institutions and foreign participation with more dispersed data, assuming the need for operational and strategic adjustments that are not necessarily due to the volume of investment but rather to the allocation Resources, for example. The most consistent data found, however, were presented in the panel analysis with the most significant effect found between the dependent variable Employees / Asset and the independent variable (CAPEX in data processing). Positive effects of CAPEX on data processing in profitability were also identified.